Peran Dinas Pariwisata dalam Meningkatkan Pendapatan Asli Daerah di Provinsi Maluku - Berny Jofrans Metwaan; Selpiah Sappe (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
Regional Original Income is one of the sources of regional financial revenue which is the main capital in carrying out development in the regions. Regional Original Income consists of Regional Taxes, Regional Levies, Proceeds from the Management of Separated Regional Assets, and Other Legitimate Original Regional Revenues. To get the maximum revenue from the original regional income, proper management is needed, therefore the researcher decided to conduct research on the management of one of the original regional income sources with the title "ROLE OF TOURISM DEPARTMENT IN IMPROVING REGIONAL ORIGINAL INCOME IN MALUKU PROVINCE". In this study the authors used a descriptive qualitative method with an inductive approach. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis technique used was data reduction, data display and conclusion drawing. Based on the results of research conducted by the author, the management that takes place at the Maluku Provincial Tourism Office starts from planning, institutional fields, marketing, creative economy and destination fields. The problem that was found was the decline in Regional Original Income over the last few years, which was caused by the natural disaster factor that was the Covid-19 pandemic which resulted in a decrease in the number of tourists. Efforts that can be made are the development of a tourism management strategy in order to attract tourist visits through activities that can increase tourist interest, improve facilities and infrastructure, improve the quality of human resources, and collaborate with all parties both inside and outside the region in order to develop available tourist destinations.